THE INTERESTS OF JUNIOR HIGH SCHOOL STUDENTS IN THE DISTRICT OF NORTH PADANG IN CHOOSING VOCATIONAL EDUCATION HIGH SCHOOL (SMK) - 556-565 , Selamet (CIVED, 2015)
Abstract This study is a quantitative descriptive research that aims to reveal how much the factors that affect the interests of junior high school students (SMP) in the District of North Padang to choose vocational high school (SMK) and find out if there is a difference interest in choosing vocational education between the students in private junior high school  and Public junior high school in the District of North Padang. The population of research was grade IX students of junior high schools in the District of North Padang  in the academic year of 2014-2015. Samples were taken using  the purposive proportional random sampling technique  with the sample size is 208 students. The instrument used was a questionnaire likert scale models and the analysis of data using the percentage degree of achievement and t- test. The results showed that the internal factors that affect the interests of junior high school students to choose vocational education amounted to 65.55 % with sufficient category, while the external factor of 57.35 % with less category/ low. As for the internal factors and external factors that affect the interests of students in private junior high school in the district of North Padang choose vocational education with an average value of the degree of achievement of 69.23 % with sufficient category, and the interest students in  public Junior High School in the District of North Padang has avarage degree of achievement of 53.93 % with very low category. In addition there is a difference interest between the public and private junior high school students in the District of North Padang with the t-table 1.9758 < 1.9806 t theory. Keywords: students interests, internal factors, external factors